Meetings: Roman Ingarden in Recollections (Wydawnictwo Księgarnia Akademicka, 2020)
Phenomenology is not a current trend in philosophy, nor is it a fashionable trend in philosophical culture. This is probably one of the reasons why research of the academic achievements of Roman Ingarden has weakened and slowed down in recent years. To some extent this is the law of history, but it is surely also, in some way, the issue of Ingarden’s very thought, the understanding of which requires effort and commitment. This publication is not yet another presentation of Ingarden’s system; nor is it an analytical penetration into the detailed problems of that system. The philosopher is depicted here through the recollections of his students who participated in his academic activities in the years 1957-1963. This is his second return to didactics in the post-war period, separated by a forced leave and a ban on teaching; the first period being the years 1945-1950. The book consists of two distinct parts. The first is introducing chapters, ranged according to an age and the level of saturation with Ingarden’s ideology. The first chapter in this section – authored by Dominika Czakon and Natalia Anna Michna – is a more personal reflection on Ingarden from the point of view of the youngest generation of philosophers. Next, an article by Monika Komaniecka-Łyp presents the history of Ingarden when he was under surveillance by the Security Service of the Polish People’s Republic, resulting from the operations aimed against the academic community of the Jagiellonian University. The last text in this section – authored by the undersigned – is of a biographical nature, where Ingarden is presented as a secondary school teacher and academic mentor. The second part of the book is a unique collection of memories of Ingarden’s two grandchildren, students, friends and associates. The work provides the reader with a large collection of photos presenting the authors of the recollections at the time of their university studies. One can also find pictures of personal memorabilia, such as student records from exams in important subjects. In the vast majority of cases, Ingarden is the main character behind both photos and scans of individual pages from the record books. At the end of the book the reader will find a list of students from particular years of the last period of his work.